Diversifikasi Pemanfaatan Buah Sukun (Artocarpus altilis) Menjadi Sereal Sebagai Alternatif Pangan Potensial - Prastika, Andika; Halida Vinkarisma, Devadha; Sultan Ali Muzakhar, Syah (Politeknik Negeri Ketapang, 2022)
Consumption of quality food with high nutrition is very important to note. Wheat cereal is one of the foods to meet daily carbohydrate needs. Consumption of wheat cereals with raw materials originating from abroad also increases, the number of imports of wheat as cereal ingredients which reaches 8 million tons is a problem that must be given a solution, one of which is by diversifying the potential of natural resources. The source of local food that has not been widely used and managed properly is breadfruit. Based on data from the Central Statistics Agency of the Republic of Indonesia, in 2020 the production of breadfruit in Indonesia is 190,551 tons. Breadfruit cereal is an innovation in the use of breadfruit which has nutrients in the form of carbohydrates, fiber, protein, vitamins, and so on so that this food product has the potential to be the product of choice in maintaining food security.